Diels–Alder Reactions of γ-Hydroxybutenolides: Approach to the Himbacine Tricyclic Core - Miles, William H.; Thamattoor, Dasan M.; Cerbone, Ryan E.; Beideman, Daniel J.; Zeiders, Samantha M.; Jasiewicz, Natalie E.; Petersen, Stephanie M.; Naimoli, Barbara J.; Leo, Joseph V.; Suarsana, Ida B. G.; George, Jason S.; Albano, Nicholas J. (Synthesis, 2016)
The Diels–Alder reaction of γ-hydroxybutenolides with dienes gave good yields of cycloadducts under thermal and Lewis acid catalyzed conditions. The application of this methodology to a more complex system was demonstrated by the synthesis of a model system for the tricyclic himbacine core. The stereo- and regioselective Diels–Alder reaction established three of the stereogenic centers, with the fourth stereogenic center secured by diastereoselective alkylation of the cycloadduct.
Keywords: γ-hydroxybutenolide; Diels–Alder reaction; himbacine; Lewis acid catalysis; isomerization